Tramadol for the treatment of pain in companion animals - Tomanić, Dragana; Kovačević, Zorana; Stojanović, Dragica; Stojanac, Nenad; Erdeljan, Mihajlo; Mihajlović, Jovan (Biologia Serbica, 2021)
For both medical and ethical reasons, the importance of providing effective pain relief for dogs and cats following surgical procedures or acute injury, as well as for those suffering from chronic medical conditions, is widely accepted. Tramadol is an opioid analgesic drug used in humans, which has become very popular in veterinary medicine. The aim of the present study was to analyze tramadol use patterns in small animal practice in Serbia in the context of current scientific literature. Study results show that the majority of prescriptions were written for dogs (65.8%) versus cats (34.2%). The most common treated conditions were digestive, orthopedic and neoplasia, etc. Regarding tramadol use, there is a large variation in administered dosage reported in the literature. Further studies are needed to fully describe the potential uses of tramadol in dogs and cats.